Establishing experimental systems for studying the replication biology of Providence virus - Walter, Cheryl Tracy (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2009)
Providence virus (PrV) is a member of the Tetraviridae, a family of small, positive sense, single-stranded RNA viruses, which characteristically infect the midgut tissue of heliothine larvae. PrV is the only known tetravirus that replicates in cultured insect cells. The virus comprises a monopartite genome resembling members of the genus Betatetravirus with the capsid precursor protein undergoing autoproteolytic cleavage at its C-terminus consistent with other tetravirus capsid precursor proteins. Analysis of viral cDNA predicted the presence of three potential overlapping gene products (from 5` to 3`): (1) p130, a protein of unrecognized nucleotide or amino acid homology with a 2A-like processing site at its N-terminus; (2) p104, the replicase ORF, which was found to be phylogenetically related to tombus-and umbraviruses replicases. The presence of a read-through stop signal in the p104 ORF was proposed to produce and amino terminal product with a predicted MW of 40 kDa (p40) and (3) the capsid protein precursor (81 kDa) which has two 2A-like processing sites at its N-terminus. Metabolic radiolabelling of viral translation products in persistently infected MG8 cells and in vitro translation of the individual ORFs were performed in order to analyse the expression of PrV gene products. p130 was translated with no evidence of 2A-like processing. Two products of 40 kDa and 104 kDa were translated from the p104 ORF, indicating that the read-through stop signal was likely to be functional. Finally, the capsid protein precursor ORF produced a major translation product of 68 kDa corresponding to the capsid protein precursor as well a peptide of 15 kDa that was attributed to the activity of the second 2A-like site at the N-terminus of the p81 ORF. The subcellular distribution of viral RNA (vRNA) and p40 in MG8 cells was investigated using immunofluorescence and biochemical fractionation. The results showed that p40/p104 and vRNA accumulated in polarized, punctate structures in some but not all MG8 cells and in some cases, co-localization was observed. This thesis concludes that PrV is a novel tetravirus with significant similarities plant carmolike viruses that should be re-classified at the family level.
Keywords: Insects -- Viruses; Insects -- Diseases; Insects -- Parasites; Host-virus relationships; RNA viruses; DNA; Insects as carriers of disease